Analysis of Financial Annual Reports for Bankruptcy Predictions Using Altman Z-Score Method - Kasman Wicaksono; Purnawarman Musa; Apriana Anggraeini Bangun; Octarina Budi Lestari; Witari Aryunani; Sigit Sukmono (Institute of Computer Science (IOCS), 2022)
The study focused on comparisons to investigate a company's financial health situation in diagnosing early bankruptcy of tobacco-producing companies using the Altman Z-Score formula. The bankruptcy risk predictions were analyzed from 2013 to 2018 on the Indonesia Stock Exchange website. The investigative data obtained at the www.idx.co.id website address used annual financial statement data from three tobacco companies in Indonesia for six consecutive years. Research illustrates that from 2013 to 2018, tobacco-producing companies are in the healthy and low-risk category. The total variable is the key to changing its health condition if it changes its value. Therefore, the results of this study can analyze the company, especially financial statements, for information on fulfilling its obligations to investors and creditors and managing assets to increase sales in generate profits.